(untitled) (TEST Ticontre. Theory Text Translation, 2023)
In Epigrammi (1961) Beppe Fenoglio imitates Martial. In this study we propose a linguistic-stylistic analysis of the work. In a comparative perspective, the translation of Martial provided by Giuseppe Lipparini and certainly read by Fenoglio is taken into account. In Epigrammi (1961) Beppe Fenoglio imita Marziale. Nel presente studio si propone un’analisi linguistico-stilistica dell’opera. In ottica comparativa, si tiene conto della traduzione di Marziale fornita da Giuseppe Lipparini e sicuramente letta da Fenoglio.